Diversity of Silica-Scaled Chrysophytes of Two Tropical Islands: Phu Quoc and Con Son (Viet Nam) - Evgeniy Gusev; Nikita Martynenko; Dmitry Kapustin; Hai Doan-Nhu; Lam Nguyen-Ngoc (Life, 2022)
The present paper focuses on the silica-scaled chrysophytes from two tropical islands: Con Son (Con Dao Archipelago) and Phu Quoc, located in Viet Nam. Electron microscopy revealed fifty-seven taxa, of which forty-one belong to the genus Mallomonas. The others are species of the genera Synura (5), Paraphysomonas (8), Spiniferomonas (1), Chrysosphaerella (1) and Lepidochromonas (1). This is the first report of the genus Lepidochromonas from Viet Nam. In addition, two species from the genus Paraphysomonas are reported for the first time in the country. Six taxa from the genus Mallomonas and five taxa from the genus Paraphysomonas were not identifiable to the lower rank and may represent new species for science. The overall diversity of the silica-scaled chrysophytes of the islands is very high. A number of rare taxa endemic to Southeast Asia were found.